Learning from Resilience Strategies in Tanzania An outlook of International Development Challenges - Gaborit, Pascaline; Olomi, Donath (Peter Lang International Academic Publishing Group, 2022)
Tanzania has been considered a model for development, peace, and stability despite the arrival of refugees from neighboring countries and the potential tensions related to climate change. Although it has accessed the rank of middleincome country, Tanzania still faces several challenges, particularly in the wake of the Covid-19 pandemic. The book aims at analyzing these challenges as well as the country's successes through a multi-disciplinary approach considering economic perspectives as well as conflict prevention, dialogue integration, climate change adaptation, forests' protection, and social perspectives - especially relating to women and girls. The current Covid situation has shaken the whole world and raised many questions on how the different regions and countries could adapt and develop resilience strategies in an uncertain and ever-changing context. Therefore, the book is not only about Tanzania but also about what we can learn from the research on Tanzania in terms of vulnerabilities and resilience strategies. This book is an outlook of International Development Challenges. This book is co-funded by the European Union in the framework of the project Pilot 4 Research and Dialogue.